2018
DOI: 10.1097/nmd.0000000000000827
|View full text |Cite
|
Sign up to set email alerts
|

Countertransference and Psychological Assessment

Abstract: Countertransference (CT) is usually conceptualized as emerging in the course of psychotherapy. This study explores whether CT manifests itself in the context of assessment and if the modality of exposure to participants (interviewer and observer) affects the intensity and nature of CT. Evaluators either led (direct exposure) or observed (indirect exposure) a 6-hour interview with a subject focusing on attachment and personality. Interviewers and evaluators then completed a measure of CT, the Therapist Response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Therapist subjective reactions (often conceptualized as CT) are a ubiquitous and potentially useful phenomenon for mental health clinicians in various diagnostic and treatment situations and settings [54,63,[111][112][113]. It is the result of a complex combination of the intrapsychic interactions of the clinician and the interpersonal dynamics between the clinician and the patient, the latter being intrinsically linked to the characteristics of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Therapist subjective reactions (often conceptualized as CT) are a ubiquitous and potentially useful phenomenon for mental health clinicians in various diagnostic and treatment situations and settings [54,63,[111][112][113]. It is the result of a complex combination of the intrapsychic interactions of the clinician and the interpersonal dynamics between the clinician and the patient, the latter being intrinsically linked to the characteristics of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we sought to empirically deepen the complex and elusive construct of CT, trying to shed some light on the relationship between CT and a session’s outcome. The complexity of the CT phenomenon—in particular its nature, both conscious and nonconscious, and the complex relationship between awareness and management of it—led us to adopt a multiperspective methodology, following the suggestions in the literature (Fauth, 2006; Hayes et al, 1997; Laverdière et al, 2018). We then explored what CT dimensions were prevalent in a sample of in-training psychotherapists conducting counseling sessions by measuring them from an internal (clinicians) and external (observers) point of view.…”
Section: Discussionmentioning
confidence: 99%
“…For example, CT could be evaluated and reported by a clinician (Rosenberger & Hayes, 2002; Tanzilli et al, 2016) or identified by an external observer (Friedman & Gelso, 2000; Van Wagoner et al, 1991); an external observer could evaluate the presence of CT starting from the therapist’s report, as happens during a typical supervision activity (Gelso et al, 2002), or detect it while observing or listening to the session in vivo (Fuertes et al, 2015; Mohr et al, 2005). Certainly, the most reliable methodological solution is to explore simultaneously the points of view of the therapist and the observer (Hayes et al, 1997; Laverdière et al, 2018) to analyze their convergence or divergence.…”
Section: Measuring Countertransference From Different Points Of Viewmentioning
confidence: 99%
“…Although researchers conducting the interviews were particularly trained for this part of the diagnostic process and prepared to attend to their personal feelings, memories, and attitudes, as well as to reflect specific interaction sequences between patients and themselves on a metalevel (Ogden, ), subjective assessments nonetheless have to be considered with extreme caution. However, research related to counter‐transference in clinical assessment contexts have shown acceptable intraclass correlation coefficients (Laverdière, Beaulieu‐Tremblay, Descôteaux, & Simard, ), substantiating that counter‐transference reactions might consist of both subjective and objective parts (Kiesler, ). Interrater reliability, though, might differ for various counter‐transference reactions (Hafkenscheid, ), and the therapists' experience of counter‐transference can occur at very different levels of reflectivity and mentalizing (Barreto & Matos, ).…”
Section: Discussionmentioning
confidence: 99%